2014
DOI: 10.1088/1748-9326/9/1/014001
|View full text |Cite
|
Sign up to set email alerts
|

Weakened tropical circulation and reduced precipitation in response to geoengineering

Abstract: Geoengineering by injection of reflective aerosols into the stratosphere has been proposed as a way to counteract the warming effect of greenhouse gases by reducing the intensity of solar radiation reaching the surface. Here, climate model simulations are used to examine the effect of geoengineering on the tropical overturning circulation. The strength of the circulation is related to the atmospheric static stability and has implications for tropical rainfall. The tropical circulation is projected to weaken un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 30 publications
10
89
3
Order By: Relevance
“…We note that Equatorial drying under a similar geoengineering scenario has also been reported in (Ferraro et al, 2014).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…We note that Equatorial drying under a similar geoengineering scenario has also been reported in (Ferraro et al, 2014).…”
supporting
confidence: 76%
“…However, the body of the presently available scientific analysis, albeit increasing (Lenton and Vaughan, 2013;Ferraro et al, 2014), is yet lacking the consideration of many more crucial aspects of the problem. For example, ours is the first attempt to conceptually categorize and frame geoengineering in terms of response theory (Kubo, 1966;Ruelle, 2009) and the theory of nonautonomous dynamical systems (Sell, 1967a, b;Romeiras et al, 1990;Crauel and Flandoli, 1994;Crauel et al, 1997;Arnold, 1998;Kloeden and Rasmussen, 2011;Carvalho et al, 2013), and then in turn as an inverse problem.…”
Section: Introductionmentioning
confidence: 99%
“…However, some of these early studies also suggested quite negative regional implications of some scenarios of deployment and were interpreted as evidence for legitimate equity concerns. Findings included, for example, that solar geoengineering had ''the potential to drive regional climates outside the envelope of greenhouse gas-induced warming, creating ''novel'' conditions'' (Irvine et al 2010: L18702); that solar geoengineering might weaken the Indian monsoon (Robock 2012); involve a large reduction in precipitation (Ferraro et al 2014;Tilmes et al 2013); or involve tradeoffs in which there would inevitably be winners and losers (Ricke et al 2010).…”
Section: Equity As Distributional Outcomes: Winners and Losers In Solmentioning
confidence: 99%
“…There are mainly two causes for the changes in the global mean precipitation. One cause is the temperature change (Bony et al, 2013;Ferraro et al, 2014;Kravitz et al, 2013b), which inflicts a feedback response due to the increased humidity in the atmosphere. The second mechanism is the temperature-independent atmospheric forcing (the change in the radiation between the surface and the top of the atmosphere) (Ferraro et al, 2014;Ferraro and Griffiths 2016).…”
Section: The Global Mean Temperature and Precipitation Responsementioning
confidence: 99%
“…One cause is the temperature change (Bony et al, 2013;Ferraro et al, 2014;Kravitz et al, 2013b), which inflicts a feedback response due to the increased humidity in the atmosphere. The second mechanism is the temperature-independent atmospheric forcing (the change in the radiation between the surface and the top of the atmosphere) (Ferraro et al, 2014;Ferraro and Griffiths 2016). This is the rapid adjustment that occurs in a short timescale, when the change in the radiative balance is compensated by the changes in the latent and sensible heat fluxes (Bala et al, 2008).…”
Section: The Global Mean Temperature and Precipitation Responsementioning
confidence: 99%